Viruses and neurodegeneration: a growing concern - S. Shouman; N. Hesham; T. Z. Salem (Journal of Translational Medicine)
Abstract Neurodegenerative diseases (NDDs) cause a progressive loss of neurons. Since NDDs are multifactorial, the precise etiology varies on the basis of the type of disease and patient history. Cohort studies and case studies have demonstrated a potential link between viral infections and the onset or progression of NDDs. Recent findings concerning the mechanisms by which neuropathic infections occur have provided more insights into the importance of such connections. In this review, we aim to elaborate on the occurrence of the neuropathic effects of viruses from epidemiological, clinical, and biological perspectives while highlighting potential treatments and challenges. One of the key players in viral neuropathogenesis is neuroinflammation caused by the immune response to the virus; this can occur due to both neurotropic and nonneurotropic viruses. The COVID-19 pandemic has raised concerns about whether vaccines are essential for preventing viruses or whether vaccines may play a part in exacerbating or accelerating NDDs. By classifying viruses and the common NDDs associated with them and further delving into their cellular pathways, this review provides insights to advance the development of potential treatments and diagnostic methods. Graphical Abstract